Adolescent psychopathology in Times of Change: The need for integrating a developmental psychopathology perspective. (June 2018) - Shulman, Shmuel; Scharf, Miri
Abstract: In addition to the major physical, sexual and cognitive changes, as well as changes in relationships with parents and peers, in recent years adolescents also have to cope with many technological changes and increasing societal instabilities. Most of the existing research has examined the extent to which increasing uncertainties might impact expression of psychopathology and its magnitude. Emerging from a developmental psychopathology perspective, we are looking first for a better understanding of the meaning that adolescents give to these changes, which in turn is likely to affect their behavior. We are also looking for better understanding the importance of the role parents, and other societal systems/institutions (such as peers) play in ameliorating or enhancing the likelihood of maladaptive adolescent behavior under these circumstances.